2022
DOI: 10.3390/nu14112312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Erythrocyte PUFA during Pregnancy with Offspring Allergy in the Chinese Population

Abstract: Findings on prenatal polyunsaturated fatty acids (PUFA) and offspring allergies have been inconsistent, and the majority of studies have focused on Western populations. This study aimed to investigate the associations between maternal erythrocyte PUFA and offspring allergies in the first 2 years in the Chinese population. We included 573 mother–infant pairs from a birth cohort. Based on the outpatient medical records, we identified the diagnosis and time of offspring allergic disease onset. We measured erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We measured erythrocyte PUFAs using gas chromatography, following the methods previously described. 25 In short, we thawed the red cell samples and added Tris-HCl buffer, which hemolyzed the cells. The resulting red blood cells were then centrifuged at for 10 min to obtain the bottom layer of milky red blood cell fragments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured erythrocyte PUFAs using gas chromatography, following the methods previously described. 25 In short, we thawed the red cell samples and added Tris-HCl buffer, which hemolyzed the cells. The resulting red blood cells were then centrifuged at for 10 min to obtain the bottom layer of milky red blood cell fragments.…”
Section: Methodsmentioning
confidence: 99%
“… 21 23 During pregnancy, PUFAs are important inflammation and immune modulators, 24 and we have shown beneficial associations of maternal PUFAs with allergic diseases in toddlers. 25 An animal study also suggested that n-3 PUFAs could combat toxicity by suppressing IgE production and improving respiratory outcomes, 26 but the results have not yet been verified in pregnant women. Further exploration of the moderating effect of PUFAs may provide insights into preventive measures against the adverse effects of air pollution for vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%